Two new species of Pleciobates (Hemiptera: Gerromorpha: Gerridae) from India, with a key to the species of Pleciobates - Jehamalar, E. Eyarin; Chandra, Kailash; Zettel, Herbert; Basu, Srimoyee; Barman, Bijita; Gupta, Susmita; Subramanian, K.a. (Zootaxa, 2014)
Two new species of water striders in the genus Pleciobates are described from India and compared with allied species. Pleciobates bengalensis Jehamalar, Basu & Zettel sp. nov. is described from the Jalpaiguri District, West Bengal and Pleciobates expositus Jehamalar, Chandra & Zettel sp. nov. (Hemiptera: Gerridae) is described from the Dhubri District, Assam. A key to the species of Pleciobates and a distribution map of the species of Pleciobates from India are provided. For the first time the genitalia of Pleciobates females are described in detail.